Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/00330124.2020.1823864
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Impact of COVID-19 on Postsecondary Teaching and Learning

Abstract: and colleges worldwide have quickly moved campus-based classes to virtual spaces due to the COVID-19 pandemic. This article explores the impact of this sudden transition of learning and teaching based on experiences and evidence from six institutions across three countries. Our findings suggest that although online and remote learning was a satisfactory experience for some students, various inequities were involved. Many students lacked appropriate devices for practical work and encountered difficulties in sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
167
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(214 citation statements)
references
References 56 publications
(52 reference statements)
12
167
0
4
Order By: Relevance
“…This transition meant taking lectures and student activities from face-to-face mode to online teaching and learning. This acculturation of pedagogical modalities at such a large-scale “might have produced the largest unplanned educational experiment ever undertaken” [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transition meant taking lectures and student activities from face-to-face mode to online teaching and learning. This acculturation of pedagogical modalities at such a large-scale “might have produced the largest unplanned educational experiment ever undertaken” [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, we only sought the views of university and secondary school students who were involved in the Project through self-report. While the use of self-report is widely supported in social science and evaluation research [ 50 ], Day and colleagues [ 33 ] suggested that “well-designed, multi-institutional, quantitative studies with large samples” (p. 10) can shed light on the impacts of remote teaching and learning. As such, future investigations may benefit from a larger, more heterogeneous sample, to include students from a wider range of academic disciplines taking various SL courses and to gather the perceptions of different stakeholders, including principals, teachers, social workers, or parents, regarding participants’ gains and their views for a more holistic picture of e-SL.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few courses that have already provided online lectures, but its ratio to face-to-face learning is still considered low. Nonetheless, moving all the existing courses online in a matter of days is a disruptive shift, in which posed as challenges faced by most faculty members due to the lack of online teaching experience, early preparation or support from educational technology teams (Bao, 2020;Bryson and Andres, 2020;Day et al, 2020;Mseleku, 2020).…”
Section: The Challengesmentioning
confidence: 99%
“…This is due to the increased availability of broadband technology and remote learning devices such as iPads or laptops for families of diverse socio-economic status, for whom travel to a university laboratory or access to paid, private pre-schooling is not possible (cf. Day et al, 2021).…”
Section: Discussionmentioning
confidence: 99%